John Coburn interviewed by Barbara Blackman - Coburn, John, 1925-2006.; Blackman, Barbara, 1928- (1986)
John Coburn, artist and tapestry maker, speaks about his early years during World War II which led him to become an artist; his conversion to Catholicism; his relationship with his wife who died of cancer in 1985; commissions undertaken for the Catholic Church; other clients for paintings and tapestries; his time in France working with the weavers at Aubusson; the curtains he designed for the Sydney Opera House; work as an art teacher and his wife's work as a printmaker.
Tape 3, side 2 and tape 7 side 2 are blank.
Recorded at Paddington, N.S.W. between 7 April 1986 and 10 April 1986.
Also available online
Timed summary available. Uncorrected transcript (typescript, 269 leaves).
Keywords: Coburn, John, -- 1925-2006 -- Interviews; Painters -- Australia -- Interviews; Textile designers -- Australia -- Interviews